Effects of high CO2 on growth, photosynthesis and respiration of Phymatolithon calcareum - Shulika, Al'ona (2014)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2014 Mäerl is a collective term for different species of non-jointed coralline red algae. Phymatolithon calcareum is a mäerl species which is widely distributed in Europe, from Norway to the Mediterranean including Portugal. In Portugal it is mostly present in the south along the coast of Algarve. This species forms highly productive marine benthic systems and is considered a priority species, protected by the European Directive 92/443/EEC - Annex V (Habitats directive). The increase of atmospheric CO2 concentration is currently leading to ocean acidification. This phenomenon is particularly worrisome for marine calcifying organism that form biogenic calcium carbonate deposits. For the present study P. calcareum was chosen as an example of calcifying species. The effect of high CO2 on the growth, photosynthesis and respiration of P. calcareum was conducted as part of a long-term mesocosm experiment. During a campaign aboard the ―Creoula‖, a search for mäerl habitats along the coast of Algarve was conducted, as a preliminary objective of this study. Three new spots were detected. The buoyant weight technique was chosen as a main method to measure growth rate. Weight increments decreased with CO2 and had a negative correlation with time. However, temperature did not had a significant effect on weight increments, neither on its own nor when combined with pCO2. At the same time, absolute growth rates were continually increasing with time and showed significant positive correlation. To investigate the effect of elevated CO2 on the photosynthesis and respiration rates of P. calcareum, light – response curves were determined in an oxygen electrode. Photosynthesis-irradiance (P-I) response curves were built up using Smiths‘ (1936) mathematical model. Photosynthesis was positively affected by elevated pCO2, while respiration increased with temperature but not with CO2.